The Role of Endothelial Cell-to-Cell Junctions in Vascular Morphogenesis - Dejana, Elisabetta; Bazzoni, Gianfranco; Lampugnani, Maria Grazia (Thrombosis and Haemostasis, 1999)
Adhesion of endothelial cells (ECs) to one another and to the extracellular matrix is mediated by various surface receptors These surface receptors belong to several families of ubiquitously expressed cell adhesion molecules, such as cadherins integrins, immunoglobulins, and proteoglycans. Besides merely providing attachment sites, most adhesive receptors interac with cytoskeletal and cytoplasmic molecules and, thus, contribute to the regulation of cell morphology and signaling.Adhesion requires refined modulation to sustain the process of new vessel formation or angiogenesis. Adjoining cells mus act in concert to finalize migration and proliferation and organize into a three-dimensional network of patent tubes. Some of the molecules involved in these cell-to-extracellular matrix and cell-to-cell interactions have now been characterized. The intracellular signaling pathways activated by these molecules are, on the contrary, still rather obscure. Moreover, the adhesive systems to matrix and neighboring cells can communicate,1-4 adding complexity and coordination to the process.